The RAMPDOOR HYDRAULIC SYSTEM MODIFICATION OF ANOA PANZER COMBAT VEHICLE - Muhammad Soleh; Dedy Pradigdo; Budi Harijanto (Jurnal Otoranpur, 2021)
Panzer Anoa 6x6 is a combat vehicle on tires where the first generation of it is made by PT Pindad (Persero). It can mobility, protection and carrying capacity. The ramp door on the Anoa 6x6 APC armored vehicle is driven by a hydraulic system to support the mobility of personnel when exiting or entering the vehicle. The components of the hydraulic system driving the Panzer Anoa 6x6 APC ram door include batteries, power packs, solenoid valves, hydraulic hoses, and hydraulic cylinders. These problems include the ramp door often not functioning, the ramp door moving too slowly and often experiencing congestion when the ramp door is working. These constraints often occur because the pump in the hydraulic system is driven by an electric motor that gets its power source from the battery. The fluid is pressed and flowed through a hydraulic pipe, then the flow of the pressurized fluid is regulated by a solenoid valve to the hydraulic cylinder to move the ramp door. This study uses a pure experimental quantitative method with empirical calculations to obtain a tool with the desired specifications. To move the ramp door weighing 200 kg with a maximum opening angle of 100 degrees in 8 seconds, the heaviest load received by the cylinder is 23557.44 N, the working pressure that occurs in the cylinder is 87.49 bar, where the fluid discharge will flow to the pump. of 2164.77 liters/minute, with a pump power of 394570 Watt and to continue the rotation of the engine with a rotation of 2814.13 rpm (idle) to the hydraulic pump using a pulley mechanism with a ratio of 1: 0.15.